Innovative slowdown, productivity reversal? - Estimating the impact of R&D on technological change - Günter Lang (Universität Augsburg, Institut für Volkswirtschaftslehre, 2002)
Motivated by the recent reversal in labor productivity growth, this paper is analyzing the relationship between R&D expenditures and productivity. Time series data of the German manufacturing industry is used to estimate a variable cost function, with the stock of knowledge being modeled as a quasifix input. The estimates show that the extracted yield is non-constant over the observation period. Current rates of return on own R&D are found to be significantly lower than during the sixties, and no signs of a significant reversal are detected. The long-term elasticity of production costs with respect to R&D reduced from –0.04 to just -0.02, the elasticity of labor demand from –0.40 to -0.15. Since the growth rates of research expenditures were also declining, the contribution of R&D to productivity growth is currently stagnating at the lowest level since 1960.
urn:nbn:de:bvb:384-opus4-712430
Keywords: D24; O31; 330; technology; innovation; research and development; productivity